2004
DOI: 10.1111/j.1365-3180.2004.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite markers and their effectiveness in Lolium temulentum

Abstract: Summary Screening a genomic library of Lolium temulentum (darnel) with synthetic (GT)15 and (GA)15 oligonucleotides, we identified microsatellite‐containing clones. Based on the sequence data of the clones, specific primer pairs were synthesized and their effectiveness examined using 10 L. temulentum and two L. persicum accessions from Asia, Africa and Europe. Fifteen primer pairs amplified single fragments, and five of them showed polymorphism in polyacrylamide gel electrophoresis in the L. temulentum and L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The Noble Foundation maintains a large world-wide collection of darnel ryegrass accessions and the genetic relatedness among these accessions has not been reported. At present, only few SSR markers are available for darnel ryegrass (Senda et al 2003). Potential use of tall fescue EST-SSR markers developed at the Noble Foundation for genetic studies in darnel ryegrass has been demonstrated Mian et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Noble Foundation maintains a large world-wide collection of darnel ryegrass accessions and the genetic relatedness among these accessions has not been reported. At present, only few SSR markers are available for darnel ryegrass (Senda et al 2003). Potential use of tall fescue EST-SSR markers developed at the Noble Foundation for genetic studies in darnel ryegrass has been demonstrated Mian et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both accessions were considered homozygous because they are autogamous species and because the codominant microsatellite loci always represented homozygous patterns for L. temulentum and L. persicum accessions in a previous study (Senda et al 2004). The crossings were performed according to Senda and Tominaga (2003).…”
Section: Methodsmentioning
confidence: 99%
“…To screen polymorphic markers, we used 311 publicly available Lolium SSR markers (Kubik et al 1999(Kubik et al , 2001Jones et al 2001Jones et al , 2002bFaville et al 2004;Senda et al 2004;Jensen et al 2005;Lauvergeat et al 2005;Gill et al 2006;Hirata et al 2006Hirata et al , 2011Studer et al 2006b;King et al 2008b). PCR reactions were performed using a three-primer PCR system (Schuelke 2000;Rampling et al 2001) in a total volume of 10 lL containing 0.5 U of Taq polymerase, 1.0 lL of 109 Taq DNA polymerase buffer, 0.4 lL of dNTP Mix (2.5 mmol L À1 each), 1 pmol forward primer, 5 pmol reverse primer, 5 pmol M13-29 primer, and 20 ng of genomic DNA.…”
Section: Pcr Amplificationmentioning
confidence: 99%